The effect of organizational citizenship behavior (OCB) on counterproductive work behavior (CWB) in sales employees : Pengaruh organizational citizenship behavior (OCB) terhadap counterproductive work behavior (CWB) pada karyawan sales - Rania Putri Shaliha; Tri Rahayuningsih; Rozi Sastra Purna (Talenta Publisher, 2023)
Counterproductive work behavior (CWB) is essential for companies to pay attention to because it makes employees violate company norms. Companies must find ways to get employees involved by highlighting Organizational Citizenship Behavior (OCB) behavior. OCB behavior can create a sense of employee attachment to the company so that it tends to avoid counterproductive attitudes. This study examines the effect of CWB on OCB in sales employees. The results of this causal study indicate that employees with high CWB behavior tend to have low OCB behavior and vice versa.